DOI: 10.22215/etd/2015-11156
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Long Range Surface Plasmon Polariton Bragg Waveguide Biosensors on Cytop and Multilayer Substrates

Abstract: This thesis documents the micro-fabrication of a Long Range Surface Plasmon Polariton (LRSPP) biosensor device design that incorporates Bragg grating waveguides. The majority of the work involved the fine tuning of the bi-layer lithography, ultraviolet (UV) exposure and metal deposition micro-fabrication procedures. The goal was to resolve very fine features, accurately produce thin metallization and achieve a high quality metal surface. Repeatable resolution of Bragg gratings having a step-in-width from 8μm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The S-grade was used as an optical cladding material in the previous work [40] [41] [42] [43]. Since the S-grade was not designed for adhesion to metal, an additional diluted M-grade was applied on the top of the cladding to improve adhesion with Au waveguides [44]. However, severe cracking issues were found when spinning the first thinner layer of CYTOP S-grade on top of the lower cladding CYTOP stack, leading to a zero yield of the whole wafer.…”
Section: Lrspp Biosensormentioning
confidence: 99%
See 4 more Smart Citations
“…The S-grade was used as an optical cladding material in the previous work [40] [41] [42] [43]. Since the S-grade was not designed for adhesion to metal, an additional diluted M-grade was applied on the top of the cladding to improve adhesion with Au waveguides [44]. However, severe cracking issues were found when spinning the first thinner layer of CYTOP S-grade on top of the lower cladding CYTOP stack, leading to a zero yield of the whole wafer.…”
Section: Lrspp Biosensormentioning
confidence: 99%
“…An additional issue is that M type CYTOP does not exhibit sufficient mechanical stability during wafer dicing [45]. Successful fabrication trials with CYTOP A-grade led to selection of this material for this research as it demonstrated good adhesion to Au waveguides and thickness could be increased through multiple coats without severe cracking issues observed in [44].…”
Section: Lrspp Biosensormentioning
confidence: 99%
See 3 more Smart Citations